2012
DOI: 10.1037/a0026063
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a broad preventive intervention for Mexican American adolescents.

Abstract: Objective This randomized trial of a family-focused preventive intervention for Mexican American (MA) adolescents evaluated intervention effects on adolescent substance use, internalizing and externalizing symptoms, and school discipline and grade records in 8th grade, one year after completion of the intervention. The study also examined hypothesized mediators and moderators of intervention effects. Method Stratified by language of program delivery (English vs. Spanish), the trial included a sample of 516 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 58 publications
(75 reference statements)
3
128
0
Order By: Relevance
“…We also expected more acculturated caregivers to participate at higher rates due to more accepting values about receiving services. Perhaps our data did not support this hypothesis because Bridges was developed and adapted through an iterative process of piloting and redesign to ensure the program was congruent with the values and preferences of Mexican American families (Gonzales et al, 2012a). We included both familism and acculturation in the model because we expected that parents in trajectory groups with higher rates of attendance would be highly acculturated but also have stronger familism values.…”
Section: Predictor Effects On Attendance Trajectories Except Sociodementioning
confidence: 96%
See 3 more Smart Citations
“…We also expected more acculturated caregivers to participate at higher rates due to more accepting values about receiving services. Perhaps our data did not support this hypothesis because Bridges was developed and adapted through an iterative process of piloting and redesign to ensure the program was congruent with the values and preferences of Mexican American families (Gonzales et al, 2012a). We included both familism and acculturation in the model because we expected that parents in trajectory groups with higher rates of attendance would be highly acculturated but also have stronger familism values.…”
Section: Predictor Effects On Attendance Trajectories Except Sociodementioning
confidence: 96%
“…Participants were 292 primary female caregivers (FCG) from families recruited for the Bridges' randomized clinical trial (RCT) that were randomly assigned to the treatment condition and attended at least one session (Gonzales et al, 2012a). Of the 542 families in the RCT, 353 were assigned to treatment; 83% (292) of FCGs from these families attended 1 or more sessions.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…by guest on April 27, 2019 www.aappublications.org/news Downloaded from preventing or reducing use of 2 substances at <12 months, 10, 21, 27 2 at 12 to 24 months, 14,20 4 at 24 to 48 months, 15,25,26,28 and 2 at >48 months. 7,18 In terms of preventing all 3 substances, 1 study showed efficacy at <12 months, 18 2 at 12 to 24 months, 18, 25 1 at 24 to 48 months, 18 and none at >48 months.…”
Section: Figurementioning
confidence: 99%